Design of instructions for evacuating disabled adults. (January 2017) - Boyce, Michael W.; Al-Awar Smither, Janan; Fisher, Daniel O.; Hancock, P.A.
Abstract: We investigated how the design of instructions can affect performance in preparing emergency stair travel devices for the evacuation of disable individuals. We had three hypotheses: 1) Design of instructions would account for a significant portion of explained performance variance, 2) Improvements in design of instructions would reduce time on task across device type and age group, and 3) There would be a performance decrement for older adults compared to younger adults based on the slowing of older adult information processing abilities. Results showed that design of instructions does indeed account for a large portion of explained variance in the operation of emergency stair travel devices, and that improvements in design of instructions can reduce time on task across device type and age group. However, encouragingly for real-world operations, results did not indicate any significant differences between older versus younger adults. We look to explore ways that individuals with disabilities can exploit these insights to enhance the performance of emergency stair travel devices for use. Highlights: Design of instructions can account for a large portion of explained variance. Improvements in design of instructions can reduce time across device type and age group. Age group (young/old) was not significantly different for time on task for assembly.